2019
DOI: 10.1016/j.heliyon.2019.e02943
|View full text |Cite
|
Sign up to set email alerts
|

Substrate specificity of thioredoxins and glutaredoxins – towards a functional classification

Abstract: The spatio-temporal reduction and oxidation of protein thiols is an essential mechanism in signal transduction in all kingdoms of life. Thioredoxin (Trx) family proteins efficiently catalyze thiol-disulfide exchange reactions and the proteins are widely recognized for their importance in the operation of thiol switches. Trx family proteins have a broad and at the same time very distinct substrate specificity – a prerequisite for redox switching. Despite of multiple efforts, the true nature for this specificity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
76
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(77 citation statements)
references
References 73 publications
0
76
0
1
Order By: Relevance
“…At present, we encounter a paradigm shift in understanding the redox network by incorporating information on structural properties and electrostatic interfaces of TRXs (Berndt et al 2015;Gellert et al 2019). The authors of the former study compared and clustered 35 TRX-fold domains in 33 proteins.…”
Section: Paradigm Shift 3: the Specificity Of Trx Arises From The Micmentioning
confidence: 99%
“…At present, we encounter a paradigm shift in understanding the redox network by incorporating information on structural properties and electrostatic interfaces of TRXs (Berndt et al 2015;Gellert et al 2019). The authors of the former study compared and clustered 35 TRX-fold domains in 33 proteins.…”
Section: Paradigm Shift 3: the Specificity Of Trx Arises From The Micmentioning
confidence: 99%
“…Of course, formation of a disulfide needs two cysteinyl residues. The interaction between Trx and a substrate critically depends on complementary electrostatic properties (45,46).…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Thioredoxin-1 (Trx-1) is a small molecular weight hydrogen donor widely present in cells and exhibits a variety of biological functions, such as antioxidant and anti-inflammatory activities. 15,16 Previous studies have shown that overexpression of Trx-1 provides effective neuroprotective effects on the brain tissue of middle cerebral artery occlusion (MCAO) mice, while inhibition of Trx-1 exacerbates the neuroinflammatory response in MCAO mice. [17][18][19] These findings provide a strong scientific basis for the clinical translational application of Trx-1.…”
Section: Introductionmentioning
confidence: 99%
“…The inhibition of the inflammatory response following acute phase reperfusion plays an important role in the treatment of cerebral infarction 2,3 . Thioredoxin‐1 (Trx‐1) is a small molecular weight hydrogen donor widely present in cells and exhibits a variety of biological functions, such as antioxidant and anti‐inflammatory activities 15,16 . Previous studies have shown that overexpression of Trx‐1 provides effective neuroprotective effects on the brain tissue of middle cerebral artery occlusion (MCAO) mice, while inhibition of Trx‐1 exacerbates the neuroinflammatory response in MCAO mice 17‐19 .…”
Section: Introductionmentioning
confidence: 99%